Alginate Adsorbent Immobilization Technique Promotes Biobutanol Production by Clostridium acetobutylicum Under Extreme Condition of High Concentration of Organic Solvent - Ye, Zhuoliang; Song, Jingyi; Zhu, Enhao; Song, Xin; Chen, Xiaohui; Hong, Xiaoting (Frontiers in Microbiology, 2018)
In Acetone-Butanol-Ethanol fermentation, bacteria should tolerate high concentrations of solvent products, which inhibit bacteria growth and limit further increase of solvents to more than 20 g/L. Moreover, this limited solvent concentration significantly increases the cost of solvent separation through traditional approaches. In this study, alginate adsorbent immobilization technique was successfully developed to assist in-situ extraction using octanol which is effective in extracting butanol but presents strong toxic effect to bacteria. The adsorbent improved solvent tolerance of Clostridium acetobutylicum under extreme condition of high concentration of organic solvent. Using the developed technique, more than 42% of added bacteria can be adsorbed to the adsorbent. Surface area of the adsorbent was more than 10 times greater than sodium alginate. Scanning electron microscope image shows that an abundant amount of pore structure was successfully developed on adsorbents, promoting bacteria adsorption. In adsorbent assisted ABE fermentation, there was 21.64 g/L butanol in extracting layer compared to negligible butanol produced with only the extractant but without the adsorbent, for the reason that adsorbent can reduce damaging exposure of Clostridium acetobutylicum to octanol. The strategy can improve total butanol production with respect to traditional culture approach by more than 2.5 fold and save energy for subsequent butanol recovery, which effects can potentially make the biobutanol production more economically practical.